A cost-effectiveness analysis of revaccination and catch-up strategies with the 23-valent pneumococcal polysaccharide vaccine (PPV23) in older adults in Japan. (3rd July 2018) - Jiang, Yiling; Yang, Xiaoqin; Taniguchi, Kazuko; Petigara, Tanaz; Abe, Machiko
Abstract: Objective: In Japan, the National Immunization Program (NIP) includes PPV23 as the primary vaccination for adults and catch-up cohorts. The Japanese Association for Infectious Diseases recommends revaccination for older adults who received primary vaccination ≥5 years earlier. The cost-effectiveness of adding revaccination and/or continuing catch-up vaccination in the NIP was evaluated from the public payer perspective in Japan. Methods: The Markov model included five health states: no pneumococcal disease, invasive pneumococcal diseases (IPD), non-bacteremic pneumococcal pneumonia (NBPP), post-meningitis sequelae, and death. Cohorts of adults aged 65–95 were followed until age 100 or death: 2014 cohort (aged 65–95, vaccinated: 2014); 2019 cohort (aged 65: 2019); and 2019 catch-up cohort (aged 70–100: 2019, unvaccinated: 2014). Strategies included: (1) vaccinate 2014 and 2019 cohorts; (2) vaccinate 2014 and 2019 cohorts and revaccinate both; (3) strategy 1 and vaccinate 2019 catch-up cohort; (4) strategy 2 and vaccinate 2019 catch-up cohort; and (5) strategy 4 and revaccinate 2019 catch-up cohort. Parameters were retrieved from global and Japanese sources, costs and QALYs discounted at 2%, and incremental cost-effectiveness ratios (ICERs) estimated. Results: Strategy 1 had the highest number of IPD and NBPP cases, and strategy 5 the lowest. Strategies 3–5 dominated strategy 1 and strategy 2 was cost-effective compared to strategy 1 (ICER: ¥1, 622, 153 per QALY gained). At a willingness-to-pay threshold of ¥5 million per QALY gained, strategy 2 was cost-effective and strategies 3–5 were cost-saving compared to strategy 1. Conclusions: Strategies including revaccination, catch-up, or both were cost-effective or cost-saving in comparison to no revaccination and no catch-up. Results can inform future vaccine policies and programs in Japan.